PERKAWINAN SAH DIMATA HUKUM MENURUT HUKUM POSITIF DI INDONESIA - Harniwati Harniwati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Provisions in law, marriage must be carried out by fulfilling the requirements and pillars of marriage. One of the requirements of the marriage is an agreement between the parties who want to carry out the marriage, including knowing the identity of each party. This means that the marriage is prohibited if it does not meet the requirements, while such a marriage which has already been (already) implemented can be annulled. Based on Article 1 of Law Number 1 of 1974, marriage is an inner and outer bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on the One Godhead. The purpose of marriage is to form a happy and eternal family with the intention of obtaining legal offspring, marriage also aims to live together with the community in a family bond. Marriage is not only a medium to realize the fulfillment of biological needs, but also in the context of worship and draw closer to God. The desire to marry will be very evident when a person has reached adulthood, namely the desire to live together between the opposite sex in a marriage bond as a means to carry out their offspring. The fact of life in pairs is explained by Allah SWT in the Qur'an Surah Addzariat verse 49 which means: And everything We created in pairs so that you remember the greatness of Allah. Marriage is regulated by religious law, so someone who will carry out a marriage must be guided by the rules regarding marriage that have been outlined by his religious law, as regulated in Article 2 paragraph (1) of Law no. 1 of 1974 which states that marriage is legal if it is carried out according to the law of each religion and belief. What is meant by the law of each religion and belief as long as it does not contradict or is not stipulated otherwise in this law.Keywords: Legal Marriage, Law, Positive Law, Indonesia.